Psychiatry Resident-Led Tutorials Increase Medical Student Knowledge and Improve National Board of Medical Examiners Shelf Exam Scores - McKean, A. J. S.; Palmer, B. A. (Academic psychiatry, 2015)
Objectives Psychiatry residents have tremendous potential as educators. The authors envisioned residents as small-group tutors, efficiently assessing and correcting knowledge deficits using cases with discussion prompts and teaching points. They empirically tested whether this improves knowledge acquisition. Methods Senior residents delivered eight tutorials during clerkship, which covered child and adolescent psychiatry, anxiety, mood, psychotic, cognitive, and substance use disorders. A 50-item multiple-choice quiz was administered at the beginning and end of clerkship. National Board of Medical Examiners (NBME) shelf exam scores from intervention year were compared to the 4 years prior to resident involvement. Results Mean score on the initial quiz was 34.5 ± 3.7 and 41.8 ± 3.5 on second attempt ( p < 0.001). Mean score for NBME psychiatry subject exam during intervention year was 83.2 ± 8.9 and for the four prior years was 78.0 ± 9.3, which was significant ( p = 0.002). Conclusions Resident-led tutorials provide an effective means of increasing psychiatric knowledge and improving performance on NBME subject exams.